The Schistosoma Granuloma: Friend or Foe? - Hams, Emily; Aviello, Gabriella; Fallon, Padraic G. (Frontiers in Immunology, 2013)
Infection of man with Schistosoma species of trematode parasite causes marked chronic morbidity. Individuals that become infected with Schistosomes may develop a spectrum of pathology ranging from mild cercarial dermatitis to severe tissue inflammation, in particular within the liver and intestines, which can lead to life threatening hepatosplenomegaly. It is well established that the etiopathology during schistosomiasis is primarily due to an excessive or unregulated inflammatory response to the parasite, in particular to eggs that become trapped in various tissue. The eggs forms the foci of a classical type 2 granulomatous inflammation, characterized by an eosinophil rich, CD4+ T helper (Th) 2 cell dominated infiltrate with additional infiltration of alternatively activated macrophages (M2). Indeed the sequela of the type 2 perioval granuloma is marked fibroblast infiltration and development of fibrosis. Paradoxically, while the granuloma is the cause of pathology it also can afford some protection, whereby the granuloma minimizes collateral tissue damage in the liver and intestines. Furthermore, the parasite is exquisitely reliant on the host to mount a granulomatous reaction to the eggs as this inflammatory response facilitates the successful excretion of the eggs from the host. In this focused review we will address the conundrum of the S. mansoni granuloma acting as both friend and foe in inflammation during infection.